AS TRANSFORMAÇÕES DAS PRÁTICAS EM EDUCAÇÃO INFANTIL NO PERÍODO DE 1960-2000: Os trabalhos dos alunos, a voz das professoras e os documentos curriculares - Toscano, Kelly Cristina Ramos (2006)
This task aims the analyzes of the transformations of the practices in infantile education in the city hall of the city of São Bernardo do Campo, in four decades, considering the political and economic changes as well as the theoretical tendencies target in the different moments investigated. For a greater approaching with the practices of the past, three elements were fundamental: the theories that support the documents and the syllabus orientation, the voice of the teachers, that through their narration could express the practices developed along the formation course of their lives and the changes along the years, the tasks produced by the pupils along the decades studied. These students tasks have been organized in parts, pointing the frequency that certain kinds of the activity happened in different periods . Besides these parts, the narration of the teachers could highlight ways in how the practices transformations happened, from the point of view of whom practices them, from these data, I have searched in the contributions of Certeau elements to understand how the historic individual teachers deal with the products that are imposed by the social order syllabus orientation and new theories transforming them and reinventing them in their quotidian practices. Key words: infantile education; practices transformation;